The Oogenic Germline Starvation Response in C. elegans - Seidel, Hannah S. (Public Library of Science, 2011)

(untitled)
Many animals alter their reproductive strategies in response to environmental stress. Here we have investigated how L4 hermaphrodites of Caenorhabditis elegans respond to starvation. To induce starvation, we removed food at 2 h intervals from very early- to very late-stage L4 animals. The starved L4s molted into adulthood, initiated oogenesis, and began producing embryos; however, all three processes were severely delayed, and embryo viability was reduced. Most animals died via ‘bagging,’ because egg-laying was inhibited, and embryos hatched in utero, consuming their parent hermaphrodites from within. Some animals, however, avoided bagging and survived long term. Long-term survival did not rely on embryonic arrest but instead upon the failure of some animals to produce viable progeny during starvation. Regardless of the bagging fate, starved animals showed two major changes in germline morphology: All oogenic germlines were dramatically reduced in size, and these germlines formed only a single oocyte at a time, separated from the remainder of the germline by a tight constriction. Both changes in germline morphology were reversible: Upon re-feeding, the shrunken germlines regenerated, and multiple oocytes formed concurrently. The capacity for germline regeneration upon re-feeding was not limited to the small subset of animals that normally survive starvation: When bagging was prevented ectopically by par-2 RNAi, virtually all germlines still regenerated. In addition, germline shrinkage strongly correlated with oogenesis, suggesting that during starvation, germline shrinkage may provide material for oocyte production. Finally, germline shrinkage and regeneration did not depend upon crowding. Our study confirms previous findings that starvation uncouples germ cell proliferation from germline stem cell maintenance. Our study also suggests that when nutrients are limited, hermaphrodites scavenge material from their germlines to reproduce. We discuss our findings in light of the recently proposed state of dormancy, termed Adult Reproductive Diapause.